Pushed out, shut out: Addressing unjust geographies of schooling and work. (1st July 2012) - Robinson, Janean; Smyth, John; Down, Barry; McInerney, Peter
In neo-liberal times educational policy and practice is being realigned more closely to the shifting imperatives of the market with damaging effects on the lives of young people. Whilst the rhetoric suggests that schools are safe, welcoming and caring environments for the benefit of all, the veracity is very different for significant numbers of marginalised students who face fragile, uncertain and unpredictable futures. This paper draws on a number of research projects in Australia to investigate the lived reality of students who are struggling to make sense of school and their transition to 'getting a job'. The research is neither impartial nor neutral. It draws on the tradition of critical policy ethnography to identify, describe and map the kinds of conditions that both constrain and enable the aspirations, dreams and hopes of young people for productive and rewarding lives. The intent is to unsettle commonsense and deficit understandings of school life that serve to oppress and marginalise the least advantaged students.